The performance of safety implementation towards accident occurrence in malaysia construction industry - Nur Sabrina, Azmi; Ezrin Hani, Sukadarin; Hanida, Abdul Aziz (Malaysian Public Health Physicians’ Association, 2020)
Reported fatal accidents in Malaysia construction industry contributed the highest number among other industries since 2009 until 2018. These statistics are alarming and elucidate the need to conduct scientific research to find the solution to solve the problem. Safety and health issues remain critical to the construction industry due to its working environment and the complexity of working practices. To prevent an accident, hazard identification is essential to construction safety management because unidentified hazards present the most unmanageable risks. Therefore, this research is conducted to help in reducing occupational accidents in the construction industry, and it can be considered worthy. This study aims to understand the triggering events, and their factors leading to fatal accidents are of significant input. The obtained data were analyzed using a statistical analysis program. Data collections of 139 numbers of respondents have been conducted in six different construction sites in east Malaysia. The result showed that there is a correlation between worker's perspective on safety management in the construction site and accident that can lead to a more fatality rate compared to other sectors. The corresponding recommendations are ultimately put forward as fatal accident prevention in construction activities. The patterns found in this paper can contribute valuable direction for formulating accident prevention strategies. In future research, reporting of an accident and near misses are essential to be further explored.